Clinical Characteristics of Kawasaki Disease in Children with Different Age Groups: A Literature Review and Retrospective Study - Huang, Baoying; Tan, Weiping; Liao, Shan; Jiang, Wei (Current Pharmaceutical Design, 2023)
Background and Objective: Kawasaki disease (KD) is an acute self-limiting systemic vascular disease commonly observed in children less than 5 years of age. The present study comparatively assesses the clinical characteristics of children diagnosed with KD in different age groups. Furthermore, a comprehensive literature review on the clinical features and diagnostic guidelines of KD is performed. Methods: This was a retrospective study conducted on the data of KD children admitted to the Sun Yat-Sen Memorial Hospital, Guangzhou, China, from January 2016 to December 2018. The children were divided into 3 age groups, including children < 1 year of age (group A, n = 66), 1-5 years of age (group B, n = 74), and children > 5 years of age (group C, n = 14). Complete clinical evaluation, hematological, and cardiovascular assessments were conducted and compared between the three groups. Results: The time of diagnosis, hemoglobin, and neutrophil ratio of children in group A were significantly lower than the other two groups (p < 0.05), while the platelet count was significantly higher (p < 0.05). The proportion of incomplete KD (iKD) was the greatest in group A (40.9%), while the proportion of children with increased coronary Z value and aseptic meningitis was greater than that in group B (p < 0.0167). Group A showed less patients with KD shock syndrome (KDSS) than the other two groups (p < 0.05). Group B showed the greatest number of patients with arthralgia compared to the other two groups (p < 0.05). Three groups showed no significant difference to intravenous immunoglobulin (IVIG) therapy (p > 0.05). Conclusion: The younger the age of KD onset, the more atypical the conditions are, with a greater risk of affecting other systems and a higher incidences of coronary artery disease. An early treatment with glucocorticoids might be helpful in older children and those with a greater high-risk KD warning score to prevent coronary injury.
Keywords: coronary artery injury